2018
DOI: 10.1001/jamadermatol.2018.3027
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Nevus Development From Age 3 to 16 Years in the Colorado Kids Sun Care Program Cohort

Abstract: IMPORTANCE Nevi are a risk factor for melanoma and other forms of skin cancer, and many of the same factors confer risk for both. Understanding childhood nevus development may provide clues to possible causes and prevention of melanoma.OBJECTIVES To describe nevus acquisition from the ages of 3 to 16 years among white youths and evaluate variation by sex, Hispanic ethnicity, and body sites that are chronically vs intermittently exposed to the sun. DESIGN, SETTING, AND PARTICIPANTS This annual longitudinal obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Dermoscopic discussion of acquired nevi (AN) requires an understanding of nevogenesis and nevus evolution. AN begin to appear during the first decade of life and increase in number during adolescence 45 . During childhood, AN most frequently have a globular pattern on dermoscopy and are located on the torso, head, and neck 46 .…”
Section: Acquired Melanocytic Nevimentioning
confidence: 99%
“…Dermoscopic discussion of acquired nevi (AN) requires an understanding of nevogenesis and nevus evolution. AN begin to appear during the first decade of life and increase in number during adolescence 45 . During childhood, AN most frequently have a globular pattern on dermoscopy and are located on the torso, head, and neck 46 .…”
Section: Acquired Melanocytic Nevimentioning
confidence: 99%
“…1 The propensity for nevus development is strongly genetically determined, 2,3 although sun exposure during childhood clearly plays a role. 4,5 Nevi are the strongest phenotypic risk factors for melanoma, 6 and they have also been associated with basal cell carcinoma (BCC) but not squamous cell carcinoma (SCC). 7,8 Several large cohort studies have reported positive associations between higher nevus counts and internal cancers including breast 9,10 and thyroid.…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly acquired in childhood and adolescence and can regress and disappear during adulthood 1 . The propensity for nevus development is strongly genetically determined, 2,3 although sun exposure during childhood clearly plays a role 4,5 . Nevi are the strongest phenotypic risk factors for melanoma, 6 and they have also been associated with basal cell carcinoma (BCC) but not squamous cell carcinoma (SCC) 7,8 …”
Section: Introductionmentioning
confidence: 99%